2021
DOI: 10.1002/joec.12155
|View full text |Cite
|
Sign up to set email alerts
|

Integrating Career and Mental Health Counseling: Necessity and Strategies

Abstract: Individuals seeking counseling might not recognize the interconnectedness of health, mental health, work, and life concerns. Counselors, however, need to be mindful that a person's wellness is interwoven with their work, life roles, and health. Research supports the interrelationship of career development and mental health as well as the effectiveness of an integrated approach to mental health and career counseling. An integrated approach from an ecological counseling perspective is proposed for conceptualizin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Although all participants experienced job loss several months prior to their interview and were still unemployed, it was hard to determine whether the emotions and reactions shared in the interview were experienced immediately following their termination or were still reoccurring. Job loss has been described as traumatic and has been compared with grief, both of which vary in length of recovery depending on the individual (Akkermans et al, 2020 ; Tang et al, 2021 ). Although many researchers agree that unemployment affects individuals at various stages, time frame is generally not specified, similar to the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although all participants experienced job loss several months prior to their interview and were still unemployed, it was hard to determine whether the emotions and reactions shared in the interview were experienced immediately following their termination or were still reoccurring. Job loss has been described as traumatic and has been compared with grief, both of which vary in length of recovery depending on the individual (Akkermans et al, 2020 ; Tang et al, 2021 ). Although many researchers agree that unemployment affects individuals at various stages, time frame is generally not specified, similar to the model used in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has explored the intersection between employment status and mental health. Those who are unemployed are more likely to experience increased stress, negative mental and physical health symptoms, and lower life satisfaction (Tang et al, 2021 ). Much of the reactionary feelings that participants felt reflected similar symptoms of mental health disorders that have resulted from quarantine mandates (Blustein et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Career development opportunities are essential for enhancing well-being and mental health. Research has shown a significant interrelationship between career development and mental health (Tang et al, 2021). emphasize the necessity and effectiveness of integrating career and mental health counseling to address these interconnected aspects (Tang et al, 2021).…”
Section: Career Development Opportunitiesmentioning
confidence: 99%
“…Psychological inflexibility and avoidance coping have connotations for perceiving the threat a situation poses. Yet the perceived threat level has implications for distress, wellbeing, and adherence to control measures [ 36 39 ]. As depicted in Fig 1 , we propose a serial mediation of the effects of psychological inflexibility on the QoL of refugees in Uganda during COVID-19 through avoidant coping, which could have affected perceptions of the threat posed by the COVID-19 situation, adherence to control measures, and mental health; and consequently, impacting on QoL.…”
Section: Introductionmentioning
confidence: 99%